The First Report of the International Cartilage Regeneration and Joint Preservation Society's Global Registry. (December 2021) - Biant, Leela C.; Conley, Caitlin W.; McNicholas, Michael J.
Objective: The International Cartilage Regeneration and Joint Preservation Society's (ICRS's) global registry, aims to be the best source of information for patients and an unbiased resource of evidence-based medicine for scientists and clinicians working to help those unfortunate enough to suffer the pain and disability associated with articular cartilage lesions. This article constitutes the scientific summary of the reports' main findings. Design: The article outlines the historical precedents in the development of orthopedic registries from the earliest tumor registries, then local arthroplasty databases that led ultimately to international collaborations between national arthroplasty and soft tissue registries. The ICRS global cartilage registry was designed from the outset as a GDPR (General Data Protection Regulation) compliant, multilingual, multinational cooperative system. It is a web-based user-friendly, live in 11 languages by end 2019, which can be accessed viahttps://cartilage.org/society/icrs-patient-registry/ . Patients and clinicians enter data by smartphone, tablet, or computer on any knee cartilage regeneration and joint preservation treatment, including the use of focal arthroplasty. Knee Injury and Osteoarthritis Outcome Score and Kujala patient-reported outcome measures are collected preoperatively, 6 months, 12 months, and annually for ten years thereafter. EQ-5D data collection will allow cost-effectiveness analysis. Strengths, weaknesses, and future plans are discussed. Results: Since inception the registry has 264 users across 50 countries. Major findings are presented and discussed, while the entire first ICRS global registry report is available athttps://cartilage.org/society/icrs-patient-registry/registry-annual-reports/ . Conclusion . A measure of the maturity of any registry is the publication of its findings in the peer reviewed literature. With the publication of its first report, the ICRS global registry has achieved that milestone.